Impact of physical activity during weekdays and weekends on fat mass among adults: 12-month cohort study - Mantovani, Alessandra Madia [UNESP]; Werneck, André Oliveira [UNESP]; Agostinete, Ricardo Ribeiro [UNESP]; Lima, Manoel Carlos Spiguel [UNESP]; Codogno, Jamile Sanches [UNESP]; Turi-Lynch, Bruna Camilo; Fernandes, Rômulo Araújo [UNESP] (FapUNIFESP (SciELO), 2020)
BACKGROUND: Physical activity (PA) practices seem to differ between weekdays and weekends and these pattern changes can affect body fat differently. However, previous studies did not assess the mediation effect of weekday and weekend PA on maintenance of body fat using sophisticated statistical models. OBJECTIVE: To analyze the mediation effect of PA during weekdays and weekends on maintenance of fat mass over a 12-month follow-up. DESIGN AND SETTING: Longitudinal cohort study (12 months) conducted at a public university in Pres-idente Prudente, Brazil. METHODS: A sample of 225 adults (117 females) was used. Body fatness and fat mass were assessed using dual-energy X-ray absorptiometry. PA levels were assessed using a pedometer. The statistical analysis con-sisted of paired-sample t tests, independent-sample t tests, Pearson correlations and mediation models. RESULTS: After 12 months, weekend PA had decreased while body composition indicators remained sta-ble (without changes). The correlation between fat mass at baseline and follow-up was high for both sexes (men: 0.966; women: 0.941; P-value = 0.001 for both). Moreover, PA indices were inversely but moder-ately related to fat mass at baseline and follow-up. Lastly, weekend PA mediated the association between fat mass at baseline and follow-up (P-value < 0.05) by around 2% and 4%. CONCLUSION: Weekend PA mediated the association between fat mass at baseline and fat mass after one year of follow-up among these adults. Further studies are required to investigate the association between physical activity, body fat and other variables such as dietary patterns and sleep time.
Keywords: Behavior; Body composition; Exercise; Life style